Assessment of Serum Uric Acid Levels in Patients with Acute Myocardial Infarction (Academia Journal of Medicine, 2020)
Background : Aim of the study was to discover if there is the efficacy of serum uric acid in the prognostication of myocardial infarction subjects. Subjects and Methods: A total of 200 subjects were incorporated into the research. Of them, 74 patients had ST- elevated myocardial infarction, as in 26 subjects they were diagnosed with non-ST elevation myocardial infarction. Of the total of 100 subjects in the study group, there were 70 males and 30 females. A total of 100 healthy individuals as a control group were also incorporated in the study. Serum uric acid was measured on day 0, 3, 7 as well on day 30 of MI. Results: Serum uric acid was calculated on day 0, day 3, and day 7 and on day 30 of the myocardial infarction in the case study group. The mean uric acid levels on day 0 were found to be 6.32 ± 1.45 mg/dl, mean uric acid level on day 3 was found to be 5.98 ± 0.98 mg/dl, mean uric acid level on day 7 was found to be 5.14 ± 2.18 mg/dl and mean uric acid level on day 30 was found to be 4.98 ± 0.44 mg/dl. Conclusion: Serum uric acid stages are elevated in subjects of acute MI in contrast to standard well individuals. Subjects with higher Serum uric acid levels have an elevated probability of transience and it can be measured as a marker of appalling prediction.
Keywords: Cardiac Muscle; Myocardial Infarction; Uric acid Level